Atom probe tomography research on catalytic alloys and nanoparticles - Yang, Q (2018)
Catalyst is a key component in the chemical industry, with more than 90% of total chemical products reliant on their use. However, the working mechanisms are in many cases still not fully understood. For heterogeneous catalysts, in which the reactions normally occur on solid phase materials, a better understanding of the catalytic surfaces, and how they evolve under reactive environments is recognised as the next step forward in the field. This work presents a study utilising atom probe tomography (APT), combined with an in-situ reaction cell, to understand the initial oxidation processes of catalytic NiFe and NiCo model alloy systems. In order to improve reliability of results, a protocol was developed to clean the sample surfaces by field ion evaporation, eliminate sample surface contamination before in-situ oxidation was then performed. APT was successfully applied to these alloys to characterise oxide development as a function of exposure time and temperature. APT also demonstrated surface enrichment induced by oxide formation remained after reduction of the alloy. The successful application of APT on the model alloys led to the next goal which was to associate the data to real catalytic particles. To achieve this, work was extended into the field of nanoparticle catalysts. Nanoparticles with similar compositions to the model alloys were fabricated by chemical synthesis and were examined initially by transmission electron microscopy (TEM). The main goal of this phase was to investigate the surface segregation behaviour of the particles, identifying common behaviours with the model alloys. However, the presence of residual complex chemical environments around the particles following synthesis made APT analysis difficult. Therefore, an alternative method of particle fabrication was explored to better control the resulting materials for easier application of atom probe for nanoparticle analyses. Metallic nanoparticles of Ag, AuCu, AuNi, and AuNiMo were made by an inert gas condensation method, deposited on suitable support materials and were subsequently analysed by APT, facilitated by an improved sample preparation method. Surface segregation on individual nanoparticles was detected. Together with other complementary surface-probing techniques, a complete understanding of these particles from micrometre down to the level of individual particles was achieved. The potential for APT is highlighted to play a key role in this approach to realise a complete understanding of the chemical order, microstructure in multimetallic nanoparticles designed for catalysis.